Pyramiding of bacterial leaf blight resistance genes in rice variety jyothi (PTB 39) through marker assisted selection - Kabade Pramod Gorakhanath (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2017)
As in other rice growing locales around the world, in Kerala too, various climatic, edaphic, biological, physical, physiological and socio-economic variables impact the area, production, and productivity of the rice. Bacterial blight (BB), an important biotic stress caused by Xanthomonas oryzae pv. oryzae (Xoo) assumes a huge role in deciding rice profitability in Kerala. PTB 39 (Jyothi) and Mo 16 (Uma) are both elite rice varieties of Kerala, but extremely susceptible to the bacterial blight. Since both the major rice cropping seasons (virippu and mundakan) in the state coincide with monsoons, the control of the disease through chemicals or biological agents proves inadequate owing to the washing off of the applied materials. Host- plant resistance is advocated as the most effective breeding strategy to combat the bacterial blight (BB) in contrast to the use of hazardous plant protection chemicals. Breeders have attempted to introgress disease resistance genes (R-genes) into rice cultivars to impart BB resistance. Marker-assisted selection (MAS) enables pyramiding multiple R-genes along with rapid background recovery of the recurrent parent, while maintaining the exquisite quality characteristics of rice. Considering the impact of the disease on food security and sustainability, efforts to introgress three R-genes (xa5, xa13 and Xa21) into the variety Jyothi from donor parent Improved Samba Mahsuri (ISM) through Marker Assisted Selection (MAS) were made. Further, backcrossing to Jyothi (recurrent parent) and advancing the resultant BC1F1s have resulted in production of BC2F4 generation (51 plants). The present study aimed to identify BC2F4 lines pyramided with genes (xa5, xa13 and Xa21) conferring resistance to bacterial blight using functional marker as well as R-gene linked Sequence tagged site (STS) markers. In addition, advancing the R gene introgressed BC2F4s to BC2F5 generation was also envisaged. Foreground selection of the BC2F4 individuals was done using the xa5 gene linked STS marker RG556. Restriction digestion of the PCR product of the STS marker with Dra1 restriction enzyme, resulted in production of alleles of size 238bp and 438bp in all the BC2F4 individuals including the parents, indicating the presence of R-gene xa5. Amplification of DNA of the individuals with the functional marker xa5SR further confirmed the presence of R-gene xa5 in the parents as well as in the 51 BC2F4 individuals. Restriction digestion of the PCR product of STS marker RG 136 linked to R-gene xa13, with Hinf 1, produced alleles similar to that of the recurrent parent Jyothi in all the BC2F4 individuals. This indicated the absence of R-gene xa13. The absence of gene xa13 in the BC2F4s was further confirmed by using the functional marker xa13 promoter. The analysis has resulted in the production of 280bp allele associated with the susceptible allele of R-gene xa13, indicating the absence of R-gene xa13 in all the BC2F4 plants. Foreground selection with STS marker pTA 248 to detect the presence of Xa21 gene revealed that in BC2F4 Plant No. 9 and Plant No. 21 amplicon of size 992 bp, as found in the donor parent ISM was present. This confirmed that the BC2F4s Plant No. 9 and Plant No. 21 possessed resistant allele of R-gene Xa21. Results obtained thus revealed that, of the 51 BC2F4s subjected to foreground selection, BC2F4 Plant No. 9 and Plant No. 21 were the only R- gene introgressed pyramids (xa5+ Xa21). In addition, the R-gene pyramided individuals, BC2F4 Plant No. 5, Plant No. 25 and Plant No. 27 were also selected for background screening as they were near similar to recurrent parent Jyothi with respect to plant height and days to flowering. Background profiling of the selected five BC2F4s using 50 rice microsatellite (RM) markers, revealed that the banding pattern in all the BC2F4s individuals was similar to recurrent parent in case of sixteen RM markers. This indicated that the BC2F4s possessed the same allele as in recurrent parent Jyothi at these marker loci. However, there was no consistency in banding pattern among the selected BC2F4s on genotyping with the remaining 34 RM markers. BC2F4 Plant No. 9 followed by Plant No. 21 possessed higher number of donor alleles than the other three BC2F4 individuals screened. In addition, these plants along with Plant No. 5 also registered higher number (4 nos.) of heterozygous loci. Such variations may be attributed to the segregation and independent assortment of alleles in the early backcross generations. These plants could be expected to segregate for the alleles in subsequent generation. Considering the segregation of the 50 markers, the magnitude of recovery of recurrent parent genome was found to be highest in Plant No. 5 (92.20%), followed by Plant No. 27 (91.60%), Plant No. 25 (76.40%) and Plant No. 21 (64.40%). It was found to be the least in Plant No. 9 (58.80%). This was also confirmed by graphical genotyping. The dendrogram based on molecular data grouped the individuals into two major clusters. Cluster one was monogenic with only the donor parent ISM, while cluster 2 comprised of the recurrent parent Jyothi and all the five BC2F4 individuals. The highest similarity was observed between the R gene pyramids Plant No. 9 and Plant No. 21. These plants grouped into a separate sub-cluster 2 farthest from recurrent parent Jyothi under cluster 2, while Plant No. 5 showed maximum similarity with recurrent parent Jyothi. Wide variability was observed among the BC2F4 individuals for various morphological traits. The BC2F4 plant No. 9 and Plant No. 21 were near similar to donor parent ISM with respect to plant height, leaf blade length and width, productive tillers/ plant, panicle length, spikelets and grains/ panicle, grain length and decorticated grain width. The number of productive tillers/ plant and grain length in Plant No. 5 was found to be higher than both the parents, while Plant No. 27 recorded higher grain yield per plant than both the parents. Both these plants also registered a higher value than both the parents for leaf width, panicle length, spikelet’s and grains per panicle. A near total correlation was observed between the clustering of the selected BC2F4 plant based on molecular and morphological data. The dendrogram generated out of the morphological characters indicated less similarity between the two 2-R-gene pyramids (Plant No. 9 and Plant No. 21) and recurrent parent Jyothi. The identified two 2-R-gene pyramids (BC2F4s i.e., Plant No. 9 and Plant No. 21) were backcrossed to both recurrent parent Jyothi and donor parent ISM resulting in production of BC3F1s (63 Nos.) and BC1F1s (56 Nos.) respectively. Simultaneously, selfing of these individuals resulted in production of 668 BC2F5 seeds. Modern molecular techniques make it possible to use markers and probes to track the simultaneous introgression of several R-genes into a single cultivar during a crossing programme. Foreground and background profiling of these generations can ensure precise identification of R-gene introgressed genotypes that resemble the recurrent parent Jyothi.